Surgical repair of a chronic traumatic injury of the right carpal joint in a juvenile hawksbill sea turtle (Eretmochelys imbricata). Issue 1 (16th January 2021) - Cruciani, Benoit; Barret, Mathieu; Schneider, Francis; Vergneau‐Grosset, Claire
Abstract: A free‐ranging juvenile hawksbill sea turtle ( Eretmochelys imbricata ) presented to the rehabilitation centre with a chronic full thickness laceration of the right carpal joint, leaving the distal part of the flipper attached by only 2 cm of soft tissue. Open luxation of the carpal joint was noted on radiographs. Surgical reconstruction was elected despite extensive transection and osteo‐articular damage. Soft tissues were debrided and sutured. A cerclage wire was used to improve bone apposition. A type II external skeletal fixator was placed to promote soft tissue healing and pseudojoint formation. The turtle adapted well to the external fixator. Osteolysis was documented on radiographs four weeks postoperatively, and lesions improved with florfenicol treatment. The fixator was removed 3.5 months after the procedure. A year postoperatively, the function of the operated limb was normal, and the turtle was released into the ocean.